Usefulness of serum Wisteria floribunda agglutinin‐positive Mac‐2 binding protein in children with primary sclerosing cholangitis. Issue 5 (20th December 2017) - Umetsu, Shuichiro; Inui, Ayano; Sogo, Tsuyoshi; Komatsu, Haruki; Fujisawa, Tomoo
Abstract : Background: Wisteria floribunda agglutinin‐positive Mac‐2 binding protein (WFA + ‐M2BP) is a novel serum marker of hepatic fibrosis in adults with chronic hepatitis C. However, it remains unclear whether serum WFA + ‐M2BP levels are associated with the progression of liver histology in primary sclerosing cholangitis (PSC). Methods: Twenty‐eight children and adolescents with pediatric‐onset PSC (male : female patient ratio,  20:8; median age at diagnosis, 9 years) were enrolled in this study. The relation between serum WFA + ‐M2BP levels and clinical characteristics was retrospectively evaluated. Moreover, receiver operating characteristic (ROC) analysis was used to determine whether serum WFA + ‐M2BP levels could be a reliable marker to identify PSC patients with advanced liver histology. Results: According to the Ludwig classification of liver histological stage, 28 patients were classified into the four stages. The WFA + ‐M2BP level, aspartate aminotransferase (AST) to platelet ratio index (APRI), and hyaluronic acid correlated significantly with liver histological stage. Moreover, WFA + ‐M2BP showed a significant positive correlation ( P  < 0.05) with autoimmune hepatitis overlap, AST, alanine aminotransferase (ALT), γ‐glutamyltransferase, total bilirubin, immunoglobulin G, APRI, and hyaluronic acid. A ROC analysis was undertaken to distinguish the patients with advanced stage disease (stage 3–4) from those with early stage disease (stage 0–2). It showed that WFA + ‐M2BP yielded the highest area under the ROC curve value (0.898) among four surrogate makers (APRI, 0.850; Fibrosis‐4 index, 0.806; and AST/ALT ratio, 0.802). Moreover, WFA + ‐M2BP yielded the highest sensitivity, specificity, positive predictive value, and negative predictive value among the four markers. Conclusions: Serum WFA + ‐M2BP levels are useful to identify patients with advanced liver histology in pediatric PSC.